Determination of gamma oryzanol in rice bran oil by HPLC with molecularly imprinted solid-phase extraction - W. Thongchai (2018)
A molecularly imprinting technique can be used for the separation of gamma oryzanol which gives high selectivity and affinity towards template molecules. This technique was successfully applied for the molecularly imprinted polymer (MIP) synthesis via photopolymerization method by using diethylaminoethyl methacrylate (DMAEMA) as a function monomer, gamma oryzanol as template, dodecanol as porogen, 2,2'-dimethoxy-2-phenylacetophenone (DMPA) as initiator and ethylene glycol dimethacrylate (EGDMA) as cross-linker. The interaction effects (amounts of template, porogen, and cross-linker) on adsorption capacity of MIP were investigated. The strongest interaction is between the amount of porogen and the amount of cross-linker. The result of the MIP synthesis was found that 0.75 mmol of gamma oryzanol, 5 mmol of DMAEMA, 6.80 mL of dodecanol, 24.5 mmol of EGDMA and 0.18 mmol of DMPA provided the highest adsorption capacity of MIP (48 μg/mg-adsorbent). The high performance liquid chromatographic method (HPLC) was developed and validated for various chromatographic conditions for determination of gamma oryzanol in rice bran oil. The sample was separated by MIP and analyzed on chromolith®flash RP-18 column (25×4.6 mm, 5 μm), using a gradient binary phase consisting of 1.8 mM cetyl trimethylammonium bromide and methanol as mobile phase. The flow rate was kept at 1.0 mL min-1. The diode array detector was set to monitor at 330 nm for gamma oryzanol. The column temperature was maintained at room temperature. Under the optimum conditions, gamma oryzanol could be determined within a concentration range of 10-50 μg mL-1which can be expressed by a correlation coefficient of 0.9960. The limit of detection and quantitation were found to be 1.90 μg mL-1and 5.70 μg mL-1respectively. The proposed method is relatively rapid and easy to perform for the separation and determination of gamma oryzanol in Thai purple rice bran oil extract.